2006
DOI: 10.1074/jbc.m604013200
|View full text |Cite|
|
Sign up to set email alerts
|

Fibronectin Increases Matrix Metalloproteinase 9 Expression through Activation of c-Fos via Extracellular-regulated Kinase and Phosphatidylinositol 3-Kinase Pathways in Human Lung Carcinoma Cells

Abstract: Matrix metalloproteinases (MMPs) 2 are a family of zinc enzymes responsible for degradation of extracellular matrix components including basement membrane collagen, interstitial collagens, fibronectin (FN), and various proteoglycans during normal remodeling and repair processes (1, 2). The potent proteolytic activities of MMPs are mainly regulated by the concomitant expression of specific tissue inhibitors of matrix metalloproteinases (3). Excessive or inappropriate expression of MMPs may contribute to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 65 publications
2
49
0
Order By: Relevance
“…There are a few studies that explore the transcriptional regulation of EP4 and transcription factor interactions in its promoter region. Studies show that a GC-rich/Sp1 binding site located within the first 80 bases of the transcription start site in the EP4 promoter region is important in transcription initiation of the EP4 gene (24), and several negative, positive and lipopolysaccharide/ serum-responsive regions are located at different areas in the mouse EP4 promoter (16). We confirmed that AP-2 sites were involved in Fn-induced EP4 gene expression using mutated EP4 constructs.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…There are a few studies that explore the transcriptional regulation of EP4 and transcription factor interactions in its promoter region. Studies show that a GC-rich/Sp1 binding site located within the first 80 bases of the transcription start site in the EP4 promoter region is important in transcription initiation of the EP4 gene (24), and several negative, positive and lipopolysaccharide/ serum-responsive regions are located at different areas in the mouse EP4 promoter (16). We confirmed that AP-2 sites were involved in Fn-induced EP4 gene expression using mutated EP4 constructs.…”
Section: Discussionsupporting
confidence: 69%
“…However, ERK played no role in the increase of EP4 expression induced by peroxisome proliferatoractivated receptor ␤/␦ activation (15), suggesting the existence of independent pathways that differ according to the stimulus. Fn activates MMP-9 via the ERK and PI3K/Akt signaling pathways in NSCLC and ovarian cancer cells (24,42,43). The inhibitor of PI3K, wortmannin, blocked the effect of Fn on stimulation of ERK phosphorylation, indicating cross-talk between the PI3K and ERK1/2 pathways in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3C, overexpression of either IB␣⌬N or TAM67 significantly blocked the TWEAKinduced activation of MMP-9 promoter in myotubes. We also studied the role of NF-B and AP-1 in TWEAK-induced expression of MMP-9 in myotubes using a reporter gene assay in which the conserved AP-1, NF-B, or SP-1 binding sites in the human MMP-9 gene promoter were mutated (30). TWEAK-induced activation of human MMP-9 promoter was significantly blocked by point mutations in either AP-1 or NF-B but not SP-1 binding site (Fig.…”
Section: Tweak Increases Mmp-9 Production In C2c12 Myotubes and In Skmentioning
confidence: 99%